Duodenal neuroendocrine tumors: Impact of tumor size and total number of lymph nodes examined. Issue 8 (3rd November 2019) - Zhang, Xu‐Feng; Wu, Xiao‐Ning; Tsilimigras, Diamantis I.; Poultsides, George; Rocha, Flavio; Abbott, Daniel E.; Fields, Ryan; Idrees, Kamran; Cho, Cliff; Maithel, Shishir K.; Pawlik, Timothy M.; ,
Abstract: Background: The current study sought to investigate the impact of tumor size and total number of LN examined (TNLE) on the incidence of lymph node metastasis (LNM) among patients with duodenal neuroendocrine tumor (dNET). Methods: Patients who underwent curative resection for dNETs between 1997‐2016 were identified from 8 high‐volume US centers. Risk factors associated with overall survival and LNM were identified and the optimal cut‐off of TNLE relative to LNM was determined. Results: Among 162 patients who underwent resection of dNETs, median patient age was 59 (interquartile range [IQR], 51‐68) years and median tumor size was 1.2 cm (IQR, 0.7‐2.0 cm); a total of 101 (62.3%) patients underwent a concomitant LND at the time of surgery. Utilization of lymphadenectomy (LND) increased relative to tumor size (≤1 cm:52.2% vs 1‐2 cm:61.4% vs >2 cm:93.8%; P < .05). Similarly, the incidence of LNM increased with dNET size (≤1 cm: 40.0% vs 1‐2 cm:65.7% vs >2 cm:80.0%; P < .05). TNLE ≥ 8 had the highest discriminatory power relative to the incidence of LNM (area under the curve = 0.676). On multivariable analysis, while LNM was not associated with prognosis (hazard ratio [HR] = 0.9; 95% confidence intervals [95%CI], 0.4‐2.3), G2/G3 tumor grade was (HR = 1.5; 95%CI, 1.0‐2.1). Conclusions: While the incidence of LNM directly correlated with tumor size, patients with dNETs ≤ 1 cm had a 40% incidence of LNM. Regional lymphadenectomy of a least 8 LN was needed to stage patients accurately.